Peran Job Satisfaction sebagai Pemediasi Pengaruh Employee Engagement dan Organizational Commitment Terhadap Employee Performance - Febria Agustianingsih; Vivin Maharani Ekowati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Management is a process of coordinating activities with the aim of time efficiency through cooperation with others. The company will be able to achieve organizational goals if it has employees with good performance. The purpose of this study was to examine the impact of employee engagement, organizational commitment on employee performance using job satisfaction as a mediation variable. This research is a quantitative study with explanatory research method to prove the research hypotheses. Data were gathered through the distribution of questionnaires to 88 respondents, and analyzed using partial least squares (PLS). The result of this study show that employee engagement directly affects employee performance, organizational commitment directly affects employee performance, Job satisfaction mediates the influence of employee engagement on employee performance and Job satisfaction mediates the influence of  organizational commitment on employee performance.